Discharge Estimation From Dense Arrays of Pressure Transducers. Issue 3 (11th March 2021) - Harlan, M. E.; Gleason, C. J.; Altenau, E. H.; Butman, D.; Carter, T.; Chu, V. W.; Cooley, S. W.; Dolan, W. D.; Durand, M. T.; Eidam, E.; Fayne, J. V.; Feng, D.; et al.
Abstract: In situ river discharge estimation is a critical component of studying rivers. A dominant method for establishing discharge monitoring in situ is a temporary gauge, which uses a rating curve to relate stage to discharge. However, this approach is constrained by cost and the time to develop the stage‐discharge rating curve, as rating curves rely on numerous flow measurements at high and low stages. Here, we offer a novel alternative approach to traditional temporary gauges: estimating Discharge via Arrays of Pressure Transducers (DAPT). DAPT uses a Bayesian discharge algorithm developed for the upcoming Surface Water Ocean Topography satellite (SWOT) to estimate in situ discharge from automated water surface elevation measurements. We conducted sensitivity tests over 4, 954 model runs on five gauged rivers and conclude that the DAPT method can robustly reproduce discharge with an average Nash‐Sutcliffe Efficiency (NSE) of 0.79 and Kling‐Gupta Efficiency of 0.78. Further, we find that the DAPT method estimates discharge similarly to an idealized temporary gauge created from the same input data (NSE differences of less than 0.1), and that results improve significantly with accurate priors. Finally, we test the DAPT method in nine poorly gauged rivers in a realistic and complex field setting in the Peace‐Athabasca Delta, and show that the DAPT method largely outperforms a temporary gauge in this time and budget constrained setting. We therefore recommend DAPT as an effective tool for in situ discharge estimation in cases where there is not enough time or resources to develop a temporary gauge. Key Points: We adapt a discharge algorithm designed for an upcoming satellite mission for in situ discharge estimation The method relies on an array of pressure transducers installed along a mass conserved channel Estimating river discharge using multiple pressure transducers is a viable alternative to installing a temporary gauge